Characterization of Nepalese Barley Gene Pool for Leaf Rust Resistance - Amgai, Resham Babu; Pantha, Sumitra; Bhatta, Madan Raj (Nepal Journal of Biotechnology, 2016)
Barley (Hordeum vulagare L) is the major crop for the people living in the high hills and mountainous region of Nepal. Leaf rust (caused by Puccinia hordei) is one of the major production threats for barley cultivation. A lot of variation can be observed on Nepalese barley accessions with respect to leaf rust resistance characteristics. Two hundred and forty one barley accessions were screened for leaf rust resistance characteristics on heading stage at Khumaltar, Lalitpur, Nepal. Among them, one hundred and nine Nepalese barley accessions showing promising for disease resistance were screened using six SSR markers linked to leaf rust resistance genes. Bonus and Local Jau was used as the resistant and susceptible check respectively. Leaf rust resistance genes Rph1, Rph2, Rph3, Rph7, QBLR-P and QTL on chromosome 5HS were detected on Nepalese barley accessions using respective SSR markers. Eight Nepalese barley accessions showed presence of three and more leaf rust resistant genes. The poor relationship between the field disease resistance and molecular markers linked with specific leaf rust resistance gene proved that Nepalese barley gene pool contains other leaf resistance genes.